A knockdown gene approach identifies an insect vector membrane protein with leucin-rich repeats as one of the receptors for the VmpA adhesin of flavescence dorée phytoplasma - Canuto, Francesca; Duret, Sybille; Dubrana, Marie-Pierre; Claverol, Stéphane; Malembic-Maher, Sylvie; Foissac, Xavier; Arricau-Bouvery, Nathalie (Frontiers in Cellular and Infection Microbiology, 2023)
The adhesion of flavescence dorée phytoplasma to the midgut epithelium cells of their insect vectors is partially mediated by the Variable Membrane Protein A (VmpA), an adhesin which shows lectin properties. In order to identify the insect receptor for VmpA, we identified Euscelidius variegatus cells proteins interacting with recombinant VmpA-His6 by mass spectrometry analysis of VmpA-E. variegatus protein complexes formed upon in vitro interaction assays. Thirteen candidate proteins possessing potential N-glycosylation sites and predicted transmembrane domains were selected. To assess their impact in VmpA binding, we reduced the expression of the candidate genes on E. variegatus cells in culture by dsRNAmediated RNAi. The effect of candidate gene knockdown on VmpA binding was measured by the capacity of E. variegatus cells to bind VmpA-coated fluorescent beads. The decrease of expression of an unknown transmembrane protein with Leucine Rich Repeat domains (uk1_LRR) was correlated with the decreased adhesion of VmpA-beads to E. variegatus cells.The uk1_LRR was more expressed in digestive tubes than salivary glands of E. variegatus.